PENGARUH LINGKUNGAN KELUARGA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI KELAS IX MTS NEGERI 1 KOTA MAKASSAR: PENGARUH LINGKUNGAN KELUARGA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI KELAS IX - Riswan Ahmad Hidayat, Riswan; Ilyas Thahir, Ilyas; Nengsi, Ratika; Syahid, Akhmad; aidil, Muh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The main problem examined in this study is how the family environment influences the learning motivation of Grade IX students at MTs Negeri 1 Kota Makassar. This study aims to: (1) describe the family environment of students in Grade IX at MTs Negeri 1 Kota Makassar; (2) describe the learning motivation of students in Grade IX at MTs Negeri 1 Kota Makassar; and (3) analyze the extent to which the family environment influences students' learning motivation in Grade IX at MTs Negeri 1 Kota Makassar. This research is a quantitative study using a correlational approach to determine whether there is an influence between the family environment variable and learning motivation, namely the family environment variable (X) and the learning motivation variable (Y). The study was conducted at MTs Negeri 1 Kota Makassar, with a population consisting of 500 Grade IX students. The data collection techniques used were questionnaires and documentation. The data analysis techniques used include validity tests, reliability tests, classical assumption tests, and hypothesis tests. The results of the study show that the family environment of Grade IX students is generally in the medium category, as is the students' learning motivation. The study found a significant influence of the family environment on students' learning motivation. This can be seen from the statistical analysis using the t-test and f-test, where the t-test results showed that X1 had no significant effect (sig > 0.05), while X2 significantly affected variable Y. The f-test results indicated that both X1 and X2 significantly influenced variable Y, with a significance value of 0.00 < 0.05. These results indicate that the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. Thus, it can be concluded that the family environment influences the learning motivation of students at MTs Negeri 1 Kota Makassar.